Molecular and Functional Insights Into the Pulmonary Vasculature (Advances in Anatomy, Embryology and Cell Biology,, 2018)
This book provides a comprehensive review of the structure, function and pathophysiology of the pulmonary vasculature. Emerging evidence reveals the multifaceted roles played by the pulmonary vasculature. To reflect those roles, the individual chapters address topics ranging from pulmonary blood vessel development to vascular endothelial apoptosis, and delve deeply into our current understanding of various aspects of the pulmonary vasculature.